2016
DOI: 10.3389/fmicb.2016.01463
|View full text |Cite
|
Sign up to set email alerts
|

Pyrethroid-Degrading Microorganisms and Their Potential for the Bioremediation of Contaminated Soils: A Review

Abstract: Pyrethroid insecticides have been used to control pests in agriculture, forestry, horticulture, public health and for indoor home use for more than 20 years. Because pyrethroids were considered to be a safer alternative to organophosphate pesticides (OPs), their applications significantly increased when the use of OPs was banned or limited. Although, pyrethroids have agricultural benefits, their widespread and continuous use is a major problem as they pollute the terrestrial and aquatic environments and affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
120
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(127 citation statements)
references
References 109 publications
5
120
0
2
Order By: Relevance
“…In this study, we identified a novel bacterial isolate S. succinus HLJ-10 having superb D-cyphenothrin degradation activity. Strain HLJ-10 utilized D-cyphenothrin as the sole carbon source for its growth over a wide range of temperature (25-35 • C) and pH (5)(6)(7)(8)(9), indicating that the strain has excellent working ability in adverse environments. This study proves that the bacterium harbors the metabolic pathway for complete detoxification and metabolism of D-cyphenothrin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we identified a novel bacterial isolate S. succinus HLJ-10 having superb D-cyphenothrin degradation activity. Strain HLJ-10 utilized D-cyphenothrin as the sole carbon source for its growth over a wide range of temperature (25-35 • C) and pH (5)(6)(7)(8)(9), indicating that the strain has excellent working ability in adverse environments. This study proves that the bacterium harbors the metabolic pathway for complete detoxification and metabolism of D-cyphenothrin.…”
Section: Discussionmentioning
confidence: 99%
“…The optimum temperature, pH, and inoculum size at the unencoded levels were found as 31.6 • C, 7.9, and 6.05 × 10 8 CFU·mL −1 , respectively. Strain HLJ-10 was capable of rapidly degrading D-cyphenothrin without a lag phase over a wide range of temperature (25-35 • C) and pH (5)(6)(7)(8)(9). This is a very important feature of an organism for bioremediation of variable environments [30].…”
Section: Optimization Of D-cyphenothrin Degradation Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is emerging evidence that bacteria (including symbionts) are involved in the detoxification or degradation of insecticides, which may help to address pollution issues but on the other side could also promote insecticide resistance. [24][25][26][27][28] Serratia, Burkholderia, Pseudomonas and Flavobacterium spp. can degrade several different classes of insecticides.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial degradation plays an important role in the elimination of xenobiotics (18). To date, several pure bacterial cultures that are capable of degrading buprofezin have been isolated.…”
mentioning
confidence: 99%